Nilai Ajaran Inkarnasi Dalam Lakon Purbosejati - I Nyoman Murtana (Institut Seni Indonesia Denpasar, 2008)
The script of Purbasejati emphasizes the importance of “tapa-brata” (praying and fasting action) or meditation, doing con- centration to communicate and harmonize him/herself in God. To reach that level, Javanese people must control their lust as a self sublimation process and increasing soul sensitivity to get miracle and also be able to awakening and manifesting the character of God into them self. The circumstances namely “Manunggaling Kawula lan Gusti”, the unity between human being and God, a high value level in Javanese life, such as able to reach a prudent of life and life spirituality. If God is being in theur side, human will get a superiority named sekti and wicaksana. Javanese people be- lieve that in deep inside of wisdom demesnor will shine a fresh pattern of tought and do a highly valued civilization, in order to increase a dignity and prestige of life. In social life context, the wisdome attitude is very useful for society, nation and country.